Prevalence of Facial Injuries in Pediatric Population: A Cross Sectional Study from Pakistan - Hasan Tariq, Alezay Tariq, Hamza Riaz, Mohammad Umar, Mufassar Nishat, Muhammad Salman Chishty (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Road traffic accidents are the leading cause of death for children in Pakistan. This is particularly true in the country of Pakistan (RTA). Implementing safety measures such as car seats, limiting the ages of drivers in the family, and prohibiting children from riding bikes and driving cars can help prevent childhood accidents or minimise the severity of those injuries that do occur. It is difficult to appreciate the entire severity of the problem since there is a paucity of published research on the epidemiology of face injuries in children. This makes it difficult to invest in programmes that prevent injuries that are detrimental to the public’s health. Objective: To provide a description of the epidemiology of face injuries sustained by children who were hospitalized to the hospital as a result of RTA. Duration of Study: March 2019 to March 2020 Place of Study: Allama iqbal memorial teaching hospital Khawaja Muhammad Safdar medical college Design: Cross Sectional Patients and Methods: We gathered information on all patients younger than 16 years old who were admitted to the hospital as a result of RTA between the years 2019 and 2020. The patients were all younger than 16 years old. Comparisons were done across a broad spectrum of characteristics, such as the presence or absence of Facial Injuries and age groups, amongst others. Main Outcome Measures: facial injuries. Sample Size: 220 patients. Result: As a result of their injuries, 74 (34%) of the population that was affected suffered from some form of brain impairment, and 78 (35.6%) suffered from some form of face injury. There were thirteen children (9.1% of the total population) operating the vehicle when it was involved in the accident. It was discovered that 53.8% of the children were not wearing any kind of seatbelt or other kid safety gear while they were riding in the back seats of the car and they were under age while riding a bike. Conclusion: It should not come as a surprise that facial injuries are so prevalent in our society today. In addition, the study found that teenage driving is more prevalent than was previously believed, which calls for ongoing monitoring as well as the development of suitable treatments. Increased documentation of the use of restraints and stronger enforcement of safety laws by police can both play a substantial role in reducing the number of injuries that are associated with the use of restraints. The findings of the study highlight the necessity of combination seating or rear seating in addition to restraints that are appropriate for the child’s age in order to reduce the likelihood that youngsters would sustain injuries to their heads or faces.